Metode poučavanja koreografije u aerobici - Špehar, N.; Fučkar Reichel, K.; Gošnik, Jelka (2007)
Aerobics as a group fitness program, originating in the 1970s, continue to be very popular today, especially among female population (Francis, 1991). Its introduction marks the change in approach from basically overloading of an average trainee without adequate physical preparation and capabilities to programmed training with precisely defined parameters and methodics adapted to a specific group (Cotton, 1996). A wide spectrum of diverse programs was introduced. They had as a basis the aim to develop and maintain specific anthropologic characteristics of an individual with the emphasis on improvement of health and physical conditions as well as avoiding contraindicated exercises and motions. Choreography in aerobics should be a method to achieve specific goal, not a purpose to itself or showing off of the instructor’ s capabilities that might be inappropriate to trainee. Methodical training in aerobics is guided by three basic rules ; 1) from unknown to known, 2) from easy to difficult ; 3) from simple to complex (podvorac i Špehar, 2001). The content of choreography in aerobics is comprised of natural forms of motion, dance moves, specific steps associated with certain program and diverse set of hand gestures in logical motion structures that repeats guided by a selected musical background. Which method to use and when depends on the experience and knowledge of the instructor, but also on the capabilities of trainee. The appropriate selection of methodical exercises under the guidance of skilled and knowledgeable instructor can achieve interesting and well balance choreography. Under such conditions an aerobic class and specified exercises can be very fulfilling experience that in conjunction with appropriate planning can achieve positive physical transformation effects.
HRV